IMPLEMENTASI KEBIJAKAN PEMERINTAH TERHADAP PERIZINAN USAHA MIKRO KECIL MENENGAH DI KECAMATAN KULO KABUPATEN SIDENRENG RAPPANG - Lestari, Ayu (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
This article aims to examine the implementation of government policies regarding the licensing of Micro, Small, and Medium Enterprises (MSMEs) in Kulo District, Sidenreng Rappang Regency, and to identify factors influencing the effectiveness of policy execution. The background is based on the low rate of business license ownership among MSME actors, despite the government’s initiative to simplify licensing through the risk-based Online Single Submission (OSS) system. The approach applied is quantitative with a descriptive method. The population consists of 200 MSME actors, with a sample of 67 respondents selected using simple random sampling. Data collection was conducted using questionnaires and interviews, and analysis was performed through George C. Edwards III’s policy implementation framework, focusing on four primary variables: communication, resources, disposition, and bureaucratic structure. Findings indicate that the implementation of MSME licensing policies in Kulo District has not yet achieved full effectiveness. Communication and resource-related factors remain the primary obstacles, particularly the limited socialization, technological literacy in OSS system usage, and insufficient service facilities. Meanwhile, the disposition of government officials demonstrates adequate commitment; however, execution is constrained by a complex bureaucratic structure. These results indicate that the effectiveness of government policy implementation concerning MSME licensing in Kulo District largely depends on enhancing human resource capacity, simplifying administrative procedures, and intensifying ongoing policy socialization.